PERSEPSI PENGUNJUNG TERHADAP AGROWISATA SAPI PERAH NUSA PELANGI DI KABUPATEN MALANG - Ridwan, Ahmad; Azizah, Siti; Eka Kusumastuti, Anie (JURNAL MASTER PARIWISATA; Volume 05, Nomor 01, July 2018, 2018)
Research was conducted at Nusa Pelangi Dairy Agrotour- ism, Gubugklakah Village, Poncokusumo District, Malang Regency, starting from September 20th to October 31st, 2017. The purpose of this research were to identify profile, tourist characteristics, and tourist perception of Nusa Pelangi Dairy Agrotourism. Respondents were tourists who visited Nusa Pelangi Dairy Agrotourism with the age was more than 12 years old. The research used survey methode and analyzed by statistic descriptive and explorative descriptive. Data analysis showed that perception index of convenience and impression variable was 75,92 (high), perception index of sociability vari- able was 80,90 (high), perception index of use of facilities vari- able was 76,00 (high), perception index of access and linkage variable was 78,53 (high). It can be concluded that Nusa Pelan- gi Dairy Agroturism was a tourist attraction that located in Gubugklakah Tourist Village, Poncokusumo District, Malang Regency with temperature was 20 to 22oC, so it was suitable for dairy agrotourism development. The tourist caracteristics at Nusa Pelangi Dairy Agrotourism age ranging from 12th-21st years old, generally as student, and lived in Malang Regency. Overall tourist had good perception towards Nusa Pelangi Dairy Agroturism.